2017
DOI: 10.1111/ijfs.13533
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and antioxidant properties of peptidic fraction generated from crab (Portunus trituberculatus) shells by enzymatic hydrolysis

Abstract: The biochemical properties and in vitro antioxidant activity of the crab (Portunus trituberculatus) shell hydrolysates (CSHs) generated by pepsin and protamex hydrolysis were evaluated. The amino acids profile of CSHs showed a high percentage of essential amino acids (>36%). The hydrolysates were mainly composed of low molecular weight peptides (<3 kDa). CSHs showed excellent solubility and possessed interfacial properties, which were governed by their concentrations. The antioxidant activities of CSHs were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Edible crabs are one of the most valuable sources of human nutrition. Among the benefits of these creatures, they possess structurally diverse bioactive components including some anticancer and antioxidant agents (Jiang et al, 2017;Mohamed et al, 2017;Katran et al, 2019). Accordingly, they used as a natural source in pharmaceutical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Edible crabs are one of the most valuable sources of human nutrition. Among the benefits of these creatures, they possess structurally diverse bioactive components including some anticancer and antioxidant agents (Jiang et al, 2017;Mohamed et al, 2017;Katran et al, 2019). Accordingly, they used as a natural source in pharmaceutical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, enzymatic extraction is widely used in the pharmaceutical and food industries due to the absence of harmful chemical residues. Precision is provided by this technique, which also enhances the end product's physical, chemical, and organoleptic qualities while preserving its nutritional content [151] , [152] . However, this method still has several drawbacks, including lower yields, taste problems, general economic viability, and a lack of uniform hydrolysates.…”
Section: Crustaceans' Proteins and Related Moleculesmentioning
confidence: 99%
“…They found that fructose modification enhanced its antioxidant properties. The hydrolysates produced from the same species with pepsin and Protamex exhibited antioxidant activities in 2,2ʹ-azino-bis (3ethylbenzothiazoline-6-sulphonic acid) radical scavenging activity (ABTS-RSA), 2,2diphenyl-1-picrylhydrazyl radical scavenging activity (DPPH-RSA) and reducing power assay (RPA) (Jiang et al, 2017). Besides, astaxanthin isolated from three species of crabs such as Portunus sanguinolentus, Paralithodes brevipes, and Callinectes sapidus exhibited strong antioxidant properties (Suganya et al, 2015).…”
Section: Recentlymentioning
confidence: 99%